2021
DOI: 10.1177/03913988211016473
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of CytoSorb in a Covid-19 patient with secondary septic shock due to a sacral decubitus infection

Abstract: Septic shock is a clinical condition with high mortality (40%–70%) and morbidity. During septic shock, there is a significant release of cytokines and other inflammatory mediators that can cause damage to different organs, known as a “cytokine storm.” The cytokine storm can cause hypotension, tissue damage, metabolic acidosis, and renal failure. This clinical picture also seems to be confirmed in the context of Covid-19 patients. Hemoadsorption with CytoSorb represents an adjunctive therapy to attenuate the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This is characterized by increased inflammatory cytokines and biomarkers like IL-2, IL-6, IL-7, macrophage inflammatory protein 1-α, TNF-α, GCSF, ferritin, pro-B-type natriuretic peptide (Pro-BNP), C-reactive protein (CRP) and D-dimer [20]. Specifically, COVID-19 leads to a drastic increase in IL-6 [21] which is the significant driver of ARDS and immune dysregulation [22]. Recently published study by Rieder et al reported significant reduction in IL-6 levels post CytoSorb ® therapy for COVID-19 patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…This is characterized by increased inflammatory cytokines and biomarkers like IL-2, IL-6, IL-7, macrophage inflammatory protein 1-α, TNF-α, GCSF, ferritin, pro-B-type natriuretic peptide (Pro-BNP), C-reactive protein (CRP) and D-dimer [20]. Specifically, COVID-19 leads to a drastic increase in IL-6 [21] which is the significant driver of ARDS and immune dysregulation [22]. Recently published study by Rieder et al reported significant reduction in IL-6 levels post CytoSorb ® therapy for COVID-19 patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…34 Another published study stated the use of new extracorporeal (EC) organ support therapies, including hemoadsorption and hemoperfusion, to manage sepsis patients with COVID-19. 35 Expert recommendations on blood purification strategies in managing COVID-19 suggest cytokine filtration as adjuvant therapy. In its interim decision, US FDA authorized CytoSorb ® by giving the EUA to treat patients more than 18-year-old with a confirmed diagnosis of COVID-19 in ICU with imminent respiratory failure to reduce pro-inflammatory cytokine levels.…”
Section: Coronavirus Disease 2019 and Cytosorb®mentioning
confidence: 99%
“…However, the limited understanding of specific inflammatory responses in different pathologies and complex networks of inflammatory responses are insufficient to control the overall inflammatory response. For instance, sepsis-like syndromes may also occur due to viral per se or superimposed bacterial infections (37). Unfortunately, microorganisms cannot be identified in up to one-third of the cultures, which will hinder the timely initiation of appropriate antibiotic therapy (38).…”
Section: Introductionmentioning
confidence: 99%